X-ray monitoring of Classical Novae in the central region of M 31 - Henze, M.; Pietsch, W.; Haberl, F.; Hernanz, M.; Sala, G.; Hatzidimitriou, D.; Della Valle, M.; Rau, A.; Hartmann, D. H.; Burwitz, V.; Greiner, J. (2012)
We review recent results of the first dedicated monitoring programme for supersoft X-ray source (SSS) states of classical novae (CNe) in the central region of the Andromeda galaxy (M 31), performed in high-cadence campaigns with XMM-Newton and Chandra. After the first three years we had detected 21 novae in X-rays (17 new), thereby discovering peculiar objects and increasing the number of known M 31 novae with SSS state to 60. This is the largest sample known in any galaxy and we used it to carry out the first statistical analysis of novae in X-rays. We found several correlations between optical and SSS parameters, and carried out a simulation on the completeness of our monitoring as well as the first nova population study in X-rays. This shows that X-ray surveys of CNe populations are a powerful tool to address the open questions connected to these objects.
Keywords: CATACLYSMIC VARIABLES; Galaxies: individual: M 31; Novae; X-rays: binaries